Impact of Excessive Consumption of Alcoholic Beverages on the Occurrence Cardiopathies in Kinshasa - JD Mbilia Malembu; C Maluma Sangi; W Muhika Kasomba; E Ngoyi Muembo (Britain International for Academic Research (BIAR) Publisher, 2023)
This study is doing thesubject of the problem ofconsumptionabuseAlcoholic beverages and its impact on the health of the populationParticularly in the occurrence of cardiovascular disease in consumers. The OBJmain ectivity is to contributeto reduce excessive consumption of alcohol. This study is carried out in the Democratic Republic of Congo, in the vilE of Kinshasa Commune De LEMBA. The study has taken overto the taking of blood pressure at115 peopleRegular consumers of alcoholic bosss. The final result shows a prevalence of 15.3% ofConsumption ofAlcohol (except liqueurs) with an average of 6 bottles a day and a probability of accumulation of alcoholin the body of the order of30% (If it's Primus, Skol and Nkoy); 33% for Mutzig and Doppeland39% (Pourturbo King). These consumers have symptoms of hypertenon in 20% cases; And someCardiopathies in 27.8% cases (14% of frequent idiopathic heart palpitations; 7.8% of spontaneous vertigoes; 6% of hypotedus).